Denileukin diftitox for the treatment of cutaneous T-cell lymphoma - David Kaminetzky (Dove Medical Press, 2008)
David Kaminetzky1, Kenneth B Hymes21Division of Hematology/Oncology, New York University School of Medicine, New York, USA; 2New York University Cancer Institute, New York, USAAbstract: Cutaneous T-cell lymphoma/mycosis fungoides (CTCL/MF) is a rare lymphoproliferative disorder which can present as an indolent or as an aggressive process involving skin, lymph nodes, and blood. In stages IA, IB and IIA, it is usually managed with topical medications and phototherapy. If there is progression despite application of these treatments, or if the patient presents with a higher stage of disease, systemic chemotherapy or retinoids, rexinoids, biologic response modifiers are often necessary. Consequently, patients are often treated with a sequence of modalities and drugs. Denileukin diftitox (DD, Ontak®) is a targeted immunotoxin which has biological activity against malignancies expressing the IL-2 receptor. In addition to its unique mechanism of action, DD has a toxicity profile which does not overlap with most commonly used chemotherapeutic agents. CTCL/MF has been found be particularly susceptible to treatment with this agent. This review will describe the development DD, its proposed mechanism of action, the clinical trials which identified its utility in the treatment of CTCL/MF, the common toxicities encountered with this agent, and the management of these toxicities. In addition the incorporation of DD in the sequential treatment of CTCL/MF and data suggesting potential combination therapies employing this novel agent will be discussed.Keywords: T-cell lymphoma, mycosis fungoides, immunotoxin, cytokine therapy, denileukin diftitiox